GENDER-BASED VIOLENCE: UNEQUAL DISTRIBUTION OF POWER - Manzoor, Dr. Seema; Manzoor, Dr. Asma; Umme Hami (Journal of Peace, Development and Communication, 2023)
Globally, we see that male and female become victim of human rights violations, although these violations differ in severity and consequence. Unlike men women are more prone to violence. Studies show that aggression and violence practiced on women may be categorized as the origin of gender-based violence. These findings unequivocally show that violence is closely tied to gender inequality and the unequal allocation of power in society, both of which lower women's standing and make them less equal to males. Being a woman in such a patriarchal and culturally constructed society entails the danger of being exposed to all types of threats and abuse. Case examples are used in this qualitative research to demonstrate the thorough investigation. Depending on how men and women relate to one another, which dictates the level of power exercised, gender-based violence can take many different forms. Therefore, this crime against women can be classified as one of the following: rape, incest, harassment, sexual assault, at-work or in-school harassment, in-prison harassment, even women trafficking, and domestic abuse, etc.